Medullary colon carcinoma with microsatellite instability: case report - Mayra Wilma Martins Cardoso Soares; José Walter Feitosa Gomes; Elam Vasconcelos de Aquino; Igor Santos Costa; Gabriel Sampaio Feitosa; Mariana Macambira Noronha; Leonardo Saraiva Pontes (Brazilian Journal of Oncology)
Colorectal cancer is the third most common neoplasm and the second most lethal worldwide. The most common histological type is adenocarcinoma, characterized by its glandular pattern. Medullary colon carcinoma is a rare histological variant of colorectal cancer, characterized by a predominantly solid architecture, poorly differentiated or undifferentiated morphology, often associated with an anomalous immunophenotype and microsatellite instability. The present study reports a case in an academic service of general surgery of a 74-year-old patient who presented with a tumor of the ascending colon, histologically with an exuberant lymphocytic infiltrate, suggestive of large cell lymphoma, but which was revealed by subsequent immunohistochemistry to be medullary carcinoma of the colon with microsatellite instability.